Nitrous oxide and methane production from denitrifying woodchip bioreactors at three hydraulic residence times. (15th July 2019) - Davis, Morgan P.; Martin, Emily A.; Moorman, Thomas B.; Isenhart, Thomas M.; Soupir, Michelle L.
Abstract: Denitrifying bioreactors remove nitrate (NO3 − ) from agricultural drainage and are slated to be an integral part of nitrogen reduction strategies in the Mississippi River Basin. However, incomplete denitrification can result in nitrous oxide (N2 O) production and anaerobic conditions within bioreactors may be conducive to methane (CH4 ) production via methanogenesis. Greenhouse gas production has the potential to trade excess NO3 − in surface water with excess greenhouses gases in the atmosphere. Our study examined N2 O and CH4 production from pilot scale (6.38 m 3 ) bioreactors across three hydraulic residence times (HRTs), 2, 8, and 16 h. Production was measured from both the surface of the bioreactors and dissolved in the bioreactor effluent. Nitrous oxide and CH4 was produced across all HRTs, with the majority dissolved in the effluent. Nitrous oxide production was significantly greater ( P < 0.05) from 2 h HRTs (478.43 mg N2 O m −3 day −1 ) than from 8 (29.95 mg N2 O m −3 day −1 ) and 16 (36.61 mg N2 O m −3 day −1 ) hour HRTs. Methane production was significantly less ( P < 0.05) from 2 h HRTs (0.51 g C m 3 day −1 ) compared to 8 (1.50 g C m 3 day −1 ) and 16 (1.69 g C m 3 day −1 ) hour HRTs. The 2 h HRTs had significantly greater ( P = 0.05) impacts to climate change compared to 8 and 16 h HRTs. Results from this study suggest managing HRTs between 6 and 8 h in field bioreactors could minimize total greenhouse gas production and maximize NO3 − removal. Highlights: Nitrous oxide and methane production was found across all three hydraulic residence times. Nitrous oxide production was greatest from the shortest hydraulic residence time. Methane production was least from the shortest hydraulic residence time. Impacts to climate change were greatest at the shortest hydraulic residence time.